2010
DOI: 10.1564/21aug09
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Herbivore Repellents: Tools for Altering Plant Palatability

Abstract: O u t l o o k s o n Pe s t M a n a g e m e n t -A u g u s t 2 0 1 0 1 8 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…For instance, when crayfish are exposed to a predator odour and alarm signal simultaneously, effects are increased [43]. We are confident that we have demonstrated that fear, rather than altered palatability [36], was responsible for these results.…”
Section: Discussionsupporting
confidence: 51%
“…For instance, when crayfish are exposed to a predator odour and alarm signal simultaneously, effects are increased [43]. We are confident that we have demonstrated that fear, rather than altered palatability [36], was responsible for these results.…”
Section: Discussionsupporting
confidence: 51%
“…The volatile sulfur compounds (rotten egg odors) and short-chain aldehydes (rancid odors) produced by protein and lipid fermentation that were pervasive in each test pen at the time of PB application would not be welcome on landscape surrounding private homes, public parks, etc. Results of this bioassay support earlier contentions that the mere presence of sulfur odors is not the basis of repellency (Kimball and Nolte, 2006b). Despite the volatile sulfur compounds, poultry blood was a poor repellent because it lacked the proteins or peptides found in FM and HC that are necessary to impact seedling palatability.…”
Section: Resultssupporting
confidence: 79%
“…Field experiments commonly employ food trays that are placed within the vicinity of a predator scent and left overnight, with the leftover food (referred to as giving up density or GUD) measured as a response variable to the scent treatment (Carthey & Banks, ). Sometimes this forfeiture of food is conflated with a fear response (Kimball & Nolte, ) (Fig. ), even though animals may generally consume less food when it is placed near foul‐smelling scents.…”
Section: Neurobiological Mechanisms Underlying Prey Responsesmentioning
confidence: 99%